‘Putting An Islamic Scholar’s Hat on Psychologist’: A Framework for Integrating Islamic Concepts into Psychological Research - HARUN, MOHD FERDAUS; Mohd. Taib, Maisarah (Universitas Muhammadiyah Surakarta, 2025)
The integration of Islamic principles into psychological research has gained momentum in the last 40 years, reflecting a growing effort to establish a theologically grounded Islamic psychology paradigm. This study identifies four prevailing trends in Islamic psychological research: exploratory-descriptive studies, psychometric and validation studies, Islamically-originated research, and Islamic-psychological integrative studies. The later trend highlights the need for an integrative framework to enhance the credibility, transparency, and holistic development of Islamic psychology. However, significant challenges remain, including limited theological knowledge among Muslim psychologists and the lack of structured frameworks to guide integration efforts. To address these issues, this study introduces the Islamic-Psychological Research Integration Framework, a systematic five-step process that requires collaboration between psychologists and Islamic scholars. The framework includes identifying, evaluating, adapting, validating, and empirically testing the integrated-psychological constructs in empirical research. By aligning psychological concepts with Islamic principles, the framework mitigates researcher uncertainty while ensuring methodological and theological rigor. It provides practical guidelines for researchers seeking to bridge the gap between modern psychological methodology and Islamic principles, thereby promoting a comprehensive understanding of human behaviour. This initiative enriches both theoretical discourse and the psychological needs of Muslim communities, fostering a harmonious integration of scientific inquiry and Islamic values.